Bibliografi Beranotasi Buku Bedah di Perpustakaan Fakultas Kedokteran Universitas Andalas - Maragita, Sintia; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper aims to help users and librarians who are in the library of the Faculty of medicine Universitas Andalas in search of information or appointment behind the information. In the making of this paper will be on the stage of creation of annotated bibliographies on books in the library of surgery Faculty of medicine Universitas Andalas. This paper writing descriptive research methods with the use of the techniques of data collection, data collected from direct observation activities in the library faculty of medicine University of Andalas, as well as interviews with some of the informants. After the data obtained through observation, further identification on parts to be made for the annotated bibliography. On the basis of the discussion it was concluded that the preparation of an annotated bibliography of books in the library of surgery Faculty of medicine Universitas Andalas is done through several stages: 1) penetuan title of bibliography; 2) collection of books of surgery or search information that is all the books collected in searches and customized with a bibliography that will be created; 3) selection of books namely activity in selection creation of bibliographies in the book; 4) creation of a keyword that is adapted to the concept of knowledge covered in the book so readers can memahaami the contents of the writings of the principal; 5) examination of the manuscripts end the bibliography that is checking out the entire text of the spelling errors and punctuation as well as punctuation.Â Keyword: bibliography, library, surgery.